Radiological Response Is Associated With Better Long‐Term Outcomes and Is a Potential Treatment Target in Patients With Small Bowel Crohn's Disease. (July 2016) - Deepak, Parakkal; Fletcher, Joel G; Fidler, Jeff L; Barlow, John M; Sheedy, Shannon P; Kolbe, Amy B; Harmsen, William S; Loftus, Edward V; Hansel, Stephanie L; Becker, Brenda D; Bruining, David H
Abstract : OBJECTIVES: Crohn's disease (CD) management targets mucosal healing on ileocolonoscopy as a treatment goal. We hypothesized that radiologic response is also associated with better long‐term outcomes. METHODS: Small bowel CD patients between 1 January 2002 and 31 October 2014 were identified. All patients had pre‐therapy computed tomography enterography (CTE)/magnetic resonance enterography (MRE) with follow‐up CTE or MRE after 6 months, or 2 CTE/MREs≥6 months apart while on maintenance therapy. Radiologists characterized inflammation in up to five small bowel lesions per patient. At second CTE/MRE, complete responders had all improved lesions, non‐responders had worsening or new lesions, and partial responders had other scenarios. CD‐related outcomes of corticosteroid usage, hospitalization, and surgery were assessed using Kaplan–Meier survival analysis and multivariable Cox models. RESULTS: CD patients ( n =150), with a median disease duration of 9 years, had 223 inflamed small bowel segments (76 with strictures and 62 with penetrating, non‐perianal disease), 49% having ileal distribution. Fifty‐five patients (37%) were complete radiologic responders, 39 partial (26%), and 56 non‐responders (37%). In multivariable Cox models, complete and partial response decreased risk for steroid usage by over 50% (hazard ratio (HR)s: 0.37 (95% confidence interval (CI), 0.21–0.64); 0.45 (95% CI, 0.26–0.79)), and complete response decreased the risk of subsequent hospitalizations and surgery by over two‐thirds (HRs: HR, 0.28 (95% CI, 0.15–0.50); HR, 0.34 (95% CI, 0.18–0.63)). CONCLUSIONS: Radiological response to medical therapy is associated with significant reductions in long‐term risk of hospitalization, surgery, or corticosteroid usage among small bowel CD patients. These findings suggest the significance of radiological response as a treatment target.